A Method to be Use for Defining Effect of Environmental Friendly Facade Design Parameters on Energy Consumption for Office Buildings - Selma Uslusoy Şenyurt; Müjde Altın (Megaron, 2020)
Shading design which is part of the energy efficient facade design which is a sub-criterion of the environmental friendly building design is the shell element that provides the solar control depending on the glass-wall ratio, the climate, window orientation, selected glazing type properties. During the design process for solar control; all design variables that have significant effects on solar radiation and daylight considered with together. Within the scope of this research, shading elements that can be applied to office structures located at 38o latitude in İzmir have been studied together with glass-wall ratio and glass type design variables. A method has been used to determine the design parameters for the most effective solar control on the total energy consumption data, including the heating, cooling and lighting consumption values in the study. In this context, 2340 scenarios produced by grouping the variables including glass type, glass-wall ratio and shading element design components one by one. These scenarios were analyzed by DesignBuilder simulation program. The obtained data evaluated by correlation and regression analysis method in SPSS program and the effect of variables on energy consumption values determined.